The Effects of Job Autonomy, Organizational Learning, and Work Environment on Organizational Commitment of Public Sector Employees in the Ashanti Region of Ghana - Ahakwa, Isaac; Yang, Jingzhao; Agba Tackie, Evelyn; Afotey Odai, Leslie; Dartey, Samuel (International Journal of Scientific Research and Management (IJSRM), 2021)
Many employers and researchers across the globe have, over the years, adopted different approaches that can ensure employees' commitment to an organization. In this study, we seek to find a linkage between Job Autonomy, Organizational Learning, and Work Environment towards Organizational Commitment of public sector employees in Ghana. Data were obtained from three hundred and thirty (330) employees of five (5) Metropolitan, Municipal and Districts Assemblies (MMDAs) in the Ashanti Region of Ghana through the use of simple random probability sampling. However, three hundred and fifteen (315) accurate responses were used in the analysis due to incomplete and missing figures. Data were analyzed using partial least squared based on Structural Equation Modeling (SEM). The findings revealed that organizational learning has the greatest outcome on organizational commitment and was statistically significant at p< 0.05. This finding provides useful suggestions for institutions, employers, and policymakers to promote organizational learning among employees through in-service trainings, knowledge distribution, and group behavior. The result can serve as a practical tool to boost organizational commitment towards achieving organizational goals.